Synthesis, characterization and evaluation of fluorimetric chemosensors for ions based on diphenylimidazole derivatives - Ferreira, R. Cristina M. (2014)
The new 2,4,5-tri-substituted imidazole derivatives 2 and 3 were obtained in good yields through a Radziszewski reaction followed by alkylation. The new derivatives were characterized by the usual spectroscopic techniques and a detailed photophysical study was undertaken. The evaluation of the compounds as fluorimetric chemosensors was carried out by performing spectrofluorimetric titrations in acetonitrile in the presence of relevant organic and inorganic anions, and of alkaline, alkaline-earth and transition metal cations.